1994
DOI: 10.1002/crat.2170290525
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric studies on sodium fluoroantimonate single crystals

Abstract: Dielectric properties of grown single crystals of Na2SbF5 and Na3Sb2F9 have been carried out. The values of the dielectric constant of Na2SbF5 and Na3Sb2F9 are about 24.1 and 14.3, respectively, at temperatures from 30 °C to 250 °C and 225 °C for 100 kHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…With the increase in applied field frequency, the ions are increasingly unable to respond to the field and the dielectric loss decreases. This decrease can be attributed to the reduction of the diffusion of the ions in matrix with increasing of the frequency [74] and the reached low value of dielectric loss indicates that the produced powders are of good quality [75]. The low dielectric loss at higher frequency of the samples is of fundamental use for nonlinear optical materials in their application [76].…”
Section: Dielectric Study: a Permittivity And Loss Studiesmentioning
confidence: 97%
“…With the increase in applied field frequency, the ions are increasingly unable to respond to the field and the dielectric loss decreases. This decrease can be attributed to the reduction of the diffusion of the ions in matrix with increasing of the frequency [74] and the reached low value of dielectric loss indicates that the produced powders are of good quality [75]. The low dielectric loss at higher frequency of the samples is of fundamental use for nonlinear optical materials in their application [76].…”
Section: Dielectric Study: a Permittivity And Loss Studiesmentioning
confidence: 97%
“…It is observed that the dielectric loss decreases with increasing frequency. The low value of the dielectric loss indicates that the grown crystals are of good quality [20,21]. The higher values of tan δ at lower frequencies may be attributed to space-charge polarization owing to charged lattice defects [19].…”
Section: Dielectric Studiesmentioning
confidence: 99%
“…5a and b). The low value of dielectric loss (tan d) indicates that the grown crystals of NCP are of reasonably good quality [17]. From Fig.…”
Section: Article In Pressmentioning
confidence: 98%